The Contribution of Co-signaling Pathways to Anti-malarial T Cell Immunity - Faleiro, Rebecca; Karunarathne, Deshapriya S.; Horne-Debets, Joshua M.; Wykes, Michelle (Frontiers in Immunology, 2018)
Plasmodium spp., the causative agent of malaria, caused 212 million infections in 2016 with 445,000 deaths, mostly in children. Adults acquire enough immunity to prevent clinical symptoms but never develop sterile immunity. The only vaccine for malaria, RTS,S, shows promising protection of a limited duration against clinical malaria in infants but no significant protection against severe disease. There is now abundant evidence that T cell functions are inhibited during malaria, which may explain why vaccine are not efficacious. Studies have now clearly shown that T cell immunity against malaria is subdued by multiple the immune regulatory receptors, in particular, by programmed cell-death-1 (PD-1). Given there is an urgent need for an efficacious malarial treatment, compounded with growing drug resistance, a better understanding of malarial immunity is essential. This review will examine molecular signals that affect T cell-mediated immunity against malaria.